The Effect of the Perkins &Blythe Model on The Systematic Thinking Skills of Second-Intermediate Students in Mathematics - Prof. Faeeza Abd Al-Qadir Abd Al-Razzaq, Amani Issam Bahloul (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify the effect of using the Perkins & Blythe model on the systematic thinking skills of second-grade students in intermediate school in mathematics. The research sample consisted of (56) students of the second intermediate grade, for the first semester of the academic year (2020-2021), the (Al-Adala Secondary School for Boys) affiliated to the Diyala Education Directorate / Baquba District was chosen intentionally, and by random selection, group (A) was chosen. To represent the experimental group that was taught according to the Perkins & Blythe model, with (28) students, and group (B) to represent the control group that studied according to the usual method with (28) students, and the two groups were rewarded in the following variables (intelligence, educational level of the parents, chronological age, previous information in mathematics, and previous achievement in mathematics). The research tool was prepared, which is: a systemic thinking skills test consisting of (16) essay paragraphs, and the validity of the test was confirmed. And by using the Alpha-Cronbach equation, the stability of the test items was (0.73). After completing the experiment, the test was applied to the two research groups, and after collecting data and using appropriate statistical methods, the results of the research were as follows: There is a statistically significant difference between the experimental and control groups in the systemic thinking skills test, in favor of the experimental group. In light of the results of the research, the two researchers recommended that the Directorate of Preparation and Training in the General Directorate of Education of Diyala conduct training courses on the use of modern models and strategies in teaching, including the Perkins & Blythe model to increase the understanding process of learners, and suggest conducting a study to determine the extent to which teachers possess the skills of systemic thinking for the different academic levels